Words Matter: An Analysis of the Content and Readability of COVID-19 Information on Clinic Websites - Sakhuja, Mayank; Yelton, Brooks; Arent, Michelle A.; Noblet, Samuel; Macauda, Mark M.; Fedrick, Delores; Friedman, Daniela B. (Frontiers in Communication, 2021)
Objective: To examine content and readability of COVID-19 information on outpatient clinic websites in South Carolina. Participants: Thirty-three outpatient clinic websites. Methods: Using a multi-step search strategy, we located three COVID-19 information content sections from each website. Descriptive statistics were calculated for content section characteristics (focus, information source, target population/race, presence of graphics, mobilizing information). Flesch Reading Ease (FRE), Flesch Kincaid Grade Level (FKGL), and Simple Measure of Gobbledygook (SMOG) were used to calculate reading levels. Mann Whitney U and Kruskal Wallis tests were performed to examine readability levels by clinic type (primary care vs specialty) and content section characteristics. Results: Twenty-six clinics offered COVID-19 information; 70 content sections across all 26 clinics were analyzed. Sections focused on COVID-19 clinic policies (48.4%), prevention (22.6%), testing (19.4%), and symptoms (9.7%). 93.5% lacked target population, 41.9% provided no information source, 38.7% had no graphics, and none mentioned racial/ethnic groups. MFRE= 54.3, MFKGL = 9.9, MSMOG = 9.5. Conclusions: COVID-19 information focused mainly on clinic policy and was written at a ninth-grade skill level. Findings suggest there is opportunity for clinics to update their online content to convey more plain language and sourced information, especially for high-risk groups.